The course of the wound process after intraoral piercing with gold alloy clips in the experiment - Shatov , P. (Journal of Education, Health and Sport, 2025)
Background. Oral piercing remains an urgent problem in modern dentistry due to its growing popularity among young people. Studies show that about 5-20% of young people have oral piercings, with the tongue as the most common site, requiring attention to oral health risks. High-risk complications include tooth chipping, gum recession, tissue trauma, systemic infections, and aspiration or impaction of jewelry, necessitating immediate intervention and prevention. Aim. To determine the effect of gold alloy clips on the wound healing process in cheek and tongue tissues after implantation in experimental animals. Materials and methods. The study involved 8 chinchilla rabbits, following European standards for animal protection and the Ethics Committee protocol of Kharkiv National Medical University (№6, June 5, 2013). Gold clips were implanted in the soft tissues of the tongue and cheek. Histologic analysis was performed on days 7, 14, 28, and 60 at the Central Research Laboratory and Department of Pathological Anatomy. Samples were fixed in 10% neutral formalin, dehydrated, embedded in paraffin, sectioned at 4-5 μm, and stained with hematoxylin and eosin for general assessment and Van Gieson for connective tissue. Sections were examined and photographed using an Olympus BX-41 microscope. Results. On day 7, initial epithelialization of the tongue and cheek wound canals was observed, with epithelium covering less than a third of the canal and granulation tissue containing collagen bundles and single cells. By day 14, epithelialization progressed, covering over half the canal with high regenerative cells and ordered collagen bundles. On days 28 and 60, canals were fully epithelialized, with thickened epithelium showing acanthosis and hyperkeratosis, and subepithelial tissue as mature connective tissue with ordered collagen bundles, single cells, and no inflammation or microcirculatory disorders. Conclusions. Epithelialization of tongue and cheek wound canals progresses in stages, completing by day 60 with epithelial thickening, acanthosis, and hyperkeratosis. Subepithelial granulation tissue matures into connective tissue with ordered collagen bundles, sparse cells, and reduced vessels. The morphology indicates effective regeneration without inflammation or microcirculatory issues, confirming high recovery potential of oral tissues.